Treatment of non-healing sternum wound after open-heart surgery with allogenic platelet-rich plasma and fibrin glue-preliminary outcomes - Mohammad Abbasi Tashnizi; Mohammad Esmail Khayami; Hamid Reza Rahimi; Aliasghar Moeinipour; Ahmad Amouzeshi; Alexander M. Seifalian; Daryoush Hamidi Alamdari (Indian Journal of Plastic Surgery)
Introduction: Non-healing wound in the sternal region after coronary arteries bypass graft surgery is a serious complication. For healing a chronic wound, several novel approaches have been proposed recently such as using bone marrow stem cells, platelets and fibrin glue (PFG); but a non-invasive method is highly desirable in the first approach for treatment. The current study was undertaken to evaluate the effect of the combination of PFG in one treatment. Materials and Methods: We report on the treatment of six patients with life-threatening chronic sternum wounds, which caused septicemia with multi-drug resistant pathogens. The ulcers were extensively debrided initially and were measured and photographed at weekly intervals. The combination of PFG was applied topically on the wound after every 2 days. Results: The wounds were completely closed in five patients and significantly reduced in size in one. There was no evidence of local or systemic complications and any abnormal tissue formation, keloid or hypertrophic scarring. Conclusions: Our study suggests, in the first approach, PFG can be used safely in order to heal a non healing sternum wound following coronary artery bypass surgery.